2015
DOI: 10.3354/aei00133
|View full text |Cite
|
Sign up to set email alerts
|

Connected networks of sea lice populations: dynamics and implications for control

Abstract: In studies of the population dynamics of parasitic sea lice and the implications of outbreaks for salmon farms, several types of mathematical models have been implemented. Delay differential equation models describe the temporal dynamics of average adult lice densities over many farm sites. In contrast, larval transport models consider the relative densities of lice at farm sites by modelling larval movements between them but do not account for temporal dynamics or feedbacks created by reproduction. Finally, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Farms 16, 18, and 21 (if all farms contribute equally). On the contrary, Adams et al (2015) combined connectivity estimates with a salmon lice population dynamic model developed by Revie et al (2005) and found that management was most effective when targeting the highest receiving or influx farms, which is somewhat counter-intuitive. This finding suggests the need to include population dynamics, specifically to examine the network response to different treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Farms 16, 18, and 21 (if all farms contribute equally). On the contrary, Adams et al (2015) combined connectivity estimates with a salmon lice population dynamic model developed by Revie et al (2005) and found that management was most effective when targeting the highest receiving or influx farms, which is somewhat counter-intuitive. This finding suggests the need to include population dynamics, specifically to examine the network response to different treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated treatment cost per kg, although widely used, may be outdated (Shinn et al 2015). In addition, the parasites impact the global aquaculture industry with negative publicity (Adams et al 2015) due to the possible damage they have on the environment as a result of chemical treatments and influence on local wildlife (Ford & Myers 2008). Consequently, salmon lice are a major obstacle in any further expansion of the salmon aquaculture industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models are being combined to include transport processes that reflect local hydrodynamics and population models that detail the dynamics of sea lice populations (Gettinby et al, 2011, Adams et al, 2015Peacock et al, in press). These detailed models are being used to inform effective controls for sea lice, and will increasingly be applied to inform specific management practices for specific farms as more widespread hydrodynamic model output of sufficient resolution becomes available and quality data on lice counts is rapidly made available to managers.…”
Section: Comparison With Other Models Of Sea Lice Populationsmentioning
confidence: 99%
“…Amundrud and Murray, 2009;Adams et al, 2012;Adams et al, 2015), aspects of population modelling (e.g. Revie et al, 2005;Gettinby et al, 2011, McEwan et al, 2015, and statistical modelling such as of factors influencing lice treatment rates (Revie et al, 2003;Murray and Hall, 2014).…”
Section: Introductionmentioning
confidence: 99%